Microbiology Learning and Education Online - Guarner, Jeannette (J Clin Microbiol, 2016)
The ubiquity of devices that connect to the Internet has exploded, allowing for easy dissemination of information. Many teachers from kindergarten to universities use the information obtained online or post material they want their students to access. Online media readily places articles, books, videos, and games at our fingertips. The public in general also gathers health information from the Internet. The following review will explore what has been published regarding microbiology education and learning online and the use of electronic media by microbiologists for scientific purposes.